Nutrient accumulation, distribution and use efficiency in different bamboo plant species in north-eastern hills region of India - SINGH, K A; RAI, ARVIND K (The Indian Journal of Agricultural Sciences, 2012)
Nutrient accumulation, distribution and use efficiency in 30 bamboo plant species were studied in a 14 years old bamboosetum at ICAR Research Complex for NEH Region, Arunachal Pradesh Centre. Per cent concentration of N, P, Ca, Mn and Z n in different component of biomass had similar pattern in all the species. It was in the order of leaves > branches > stems and the concentration of K, Mg and Fe was in leaves > stems > branches. The N: P: K ratios of above ground biomass varied in different bamboo plant species (76–706 : 1 : 66–930). They showed that P was most limiting nutrient. Bamboo plant species had inherently different response to low P. Recycling of the nutrients through litters showed variability in the range of 2.7–40.9, 0.6–31.4, 1.5–21.1, 3.0–35.4, 1.0–35.4, 2.0–26.3, 0.5–8.0, 1.2–15.0 and 5.0– 39.3% of the annual uptake of N, P, K, Ca, Mg, Cu, Fe, Mn and Zn respectively, in different bamboo species. The pattern of nutrient-use efficiency was also different in 30 bamboo plant species.